Emissive Charge-Transfer States at Hybrid Inorganic/Organic Heterojunctions Enable Low Non-Radiative Recombination and High-Performance Photodetectors - Eisner, Flurin (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.